2021
DOI: 10.3389/fphar.2021.641435
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Lysophosphatidic Acid Induces Nerve Injury in LSS Patients via AKT Mediated NF-κB p65 Pathway

Abstract: Lumbar spinal stenosis (LSS) is a spinal degenerative disease, complicated with nerve injury. Lysophosphatidic acid (LPA), a kind of glycerophospholipid molecule is elevated in the initial stages of neural injury. This research aimed to investigate the patho-mechanism of nerve injury caused by LPA in LSS patients. Twenty-five LSS patients and fifteen idiopathic scoliosis patients (without neurological symptoms) were recruited from Xianyang Central Hospital of Shanxi Province. We measured the concentration of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We examined the effects of different drugs on cell activities. According to the cell viability results, TAK-242, JSH23, and paeoniflorin were used at concentrations of 10 μg/ml, 10 μM (Y. T. Chen, Wang, et al, 2021), 10 μM (Zhai, Liang, & Xu, 2021), and 50 μM (Zhang, Yang, et al, 2021), respectively.…”
Section: Cell Viability and Cytotoxicity Assaysmentioning
confidence: 99%
“…We examined the effects of different drugs on cell activities. According to the cell viability results, TAK-242, JSH23, and paeoniflorin were used at concentrations of 10 μg/ml, 10 μM (Y. T. Chen, Wang, et al, 2021), 10 μM (Zhai, Liang, & Xu, 2021), and 50 μM (Zhang, Yang, et al, 2021), respectively.…”
Section: Cell Viability and Cytotoxicity Assaysmentioning
confidence: 99%
“…Cord Neurons. Under an optical microscope, the cells had a long and spindle-shaped morphology, with long neurites In order to investigate the viability and cytotoxicity of LPA on spinal cord neurons, LDH and MTT tests were used to analyze the LDH release and viability of cells treated with 0, 0.1, 1, 10, and 20 μM LPA for 24 h [10]. The results showed that LPA dose dependently increased LDH release and reduced cell viability compared with the untreated cell.…”
Section: Lpa Effects On Cell Viability and Cytotoxicity In Spinalmentioning
confidence: 99%
“…Recent studies have found that the level of LPA in the CSF of LSS patients was significantly increased [ 1 ]. Meanwhile, another study found that LPA promoted apoptosis of spinal cord neurons and mediated LSS injury [ 10 ]. However, the molecular mechanisms of LPA involved in LSS remain obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress and central sensitization are inextricably linked to the development of neuropathic pain and its accompanying mood disorders [ 25 , 26 ]. These associated emotional disorders are also linked with neuroinflammation and high levels of proinflammatory targets such as the nuclear factor κB (NF-κB), of which the activation induces the phosphorylation of kappa-B inhibitor (p-IKBα) in the CNS and PNS [ 27 , 28 ]. Moreover, exogenous melatonin and irisin alleviated neuropathic pain-associated affective disorders and ethanol-induced behavioral deficits by suppressing the NF-κB activation pathway [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%